2019
DOI: 10.1093/ndt/gfz007
|View full text |Cite
|
Sign up to set email alerts
|

The association between longer haemodialysis treatment times and hospitalization and mortality after the two-day break in individuals receiving three times a week haemodialysis

Abstract: Abstract Background On the first haemodialysis (HD) day after the 2-day break in three times a week (3×W) in-centre HD, mortality and hospitalization are higher. If longer HD sessions prescribed 3×W is associated with a reduction in these events is unknown. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 40 publications
2
28
1
1
Order By: Relevance
“…We cannot say, however, the extent to which our findings may be generalizable to HD populations in other countries. Nevertheless, the study by Fotheringham et al [25], which was conducted in 7 European countries, yielded findings for all-cause hospitalization similar to ours: All three weekly patterns that we described are evident in their results (Fig 1B), though the authors focused attention on what we call the interdialytic-gap effect.…”
Section: Discussionsupporting
confidence: 86%
“…We cannot say, however, the extent to which our findings may be generalizable to HD populations in other countries. Nevertheless, the study by Fotheringham et al [25], which was conducted in 7 European countries, yielded findings for all-cause hospitalization similar to ours: All three weekly patterns that we described are evident in their results (Fig 1B), though the authors focused attention on what we call the interdialytic-gap effect.…”
Section: Discussionsupporting
confidence: 86%
“…Higher blood flow rate was more likely with longer hours on ICHD, whereas lower blood flood rate was associated with longer hours on HHD, which is expected in patients undergoing long hours/nocturnal HHD. Contrary to previous studies, 5,6,9,11 none of the evaluated comorbidities (diabetes mellitus, coronary artery disease, cerebrovascular disease, peripheral vascular disease and chronic lung disease) were found to be associated with treatment duration. It should be noted that various regression models were explored, but none showed a good model fit (low R ‐squared values), partly because of the limited nature of the data collected by the registry.…”
Section: Discussioncontrasting
confidence: 98%
“…In a recent study by Swaminathan et al, 86 893 American patients were initiated on ICHD, of whom 55% were treated in 631 facilities (43% of all centres) with a uniform treatment time of 3 hours per session three times per week 10 . In Europe, Fotheringham et al reported about half (52%) of patients on thrice weekly ICHD being treated for approximately 4 hours (226‐250 minutes) per session in a cohort of 19 557 prevalent patients participating in the DOPPS from 1998 to 2011, while about 29% of patients were undergoing sessions of less than 4 hours 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…144 Longer and/or more frequent dialysis schedules are generally better tolerated and result in less circulatory stress compared to short dialysis schedules. 145,146 This reflects reduced solute gradients and fluxes, including electrolytes and ultrafiltration rate. 54 Importantly, fluid removal and solute and electrolytes fluxes are potentially modifiable factors of the dialysis prescription.…”
Section: Solute Fluxmentioning
confidence: 99%